Effects of Mixing Temperature on the Mechanical Properties of Hot Mix Asphalt - Balik, Gul; Yilmaz, Mehmet; Kok, Baha Vural; Alatas, Taner (Turkish Chamber Civil Engineers, 2019)
In this study, the effects of mixing temperature on the performance of hot mix asphalt (HMA) were investigated. 5% Styrene-butadiene-styrene (SBS) and 18% America Gilsonite were used as binder modifiers. HMA samples were prepared at the mixing temperatures 10 degrees C, 15 degrees C, and 20 degrees C lower temperatures than the mixing temperature. Marshall Stability and flow, resistance to moisture-induced damage and indirect tensile fatigue tests were conducted on the hot mix asphalt samples. As a result of the experimental study, it was observed that use of additives increased the performance of the HMAs. In addition, it was seen that, in general, the stability, Marshall quotient, indirect tensile strength and fatigue life of the mixtures decreased and the flow values increased with decreasing mixing temperature.
Keywords: Mixing temperature; hot mix asphalt; styrene-butadiene-styrene; gilsonite; superpave; performance